Save-it-forward suppers : a simple strategy to save time, money, and sanity - Kane, Cyndi (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Transform leftovers from each meal into a fresh new dish and put a home-cooked dinner on the table every night with 100-plus recipes and 15 easy weekly menus, in this first cookbook by Cyndi "Hyacinth" Kane, often seen on Ree Drummond's hit Food Network show and blog, The Pioneer Woman"--